2018
DOI: 10.1021/acs.nanolett.8b03552
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Organic Spacers for Formamidinium-Based Hybrid Dion–Jacobson Two-Dimensional Perovskite Solar Cells

Abstract: Three-dimensional (3D) perovskite materials display remarkable potential in photovoltaics owing to their superior solar-to-electric power conversion efficiency, with current efforts focused on improving stability. Two-dimensional (2D) perovskite analogues feature greater stability toward environmental factors, such as moisture, owing to a hydrophobic organic cation that acts as a spacer between the inorganic layers, which offers a significant advantage over their comparatively less stable 3D analogues. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
287
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 231 publications
(300 citation statements)
references
References 31 publications
12
287
0
Order By: Relevance
“…[36][37][38][39][40] We therefore probed the long-term performance of 2D perovskite solar cells (Figure 8) by measuring the stability under inert and humid ambient air conditions ( Figure 8a and Figure S14, Supporting Information, respectively). [36][37][38][39][40] We therefore probed the long-term performance of 2D perovskite solar cells (Figure 8) by measuring the stability under inert and humid ambient air conditions ( Figure 8a and Figure S14, Supporting Information, respectively).…”
Section: Long-term Stabilitymentioning
confidence: 99%
“…[36][37][38][39][40] We therefore probed the long-term performance of 2D perovskite solar cells (Figure 8) by measuring the stability under inert and humid ambient air conditions ( Figure 8a and Figure S14, Supporting Information, respectively). [36][37][38][39][40] We therefore probed the long-term performance of 2D perovskite solar cells (Figure 8) by measuring the stability under inert and humid ambient air conditions ( Figure 8a and Figure S14, Supporting Information, respectively).…”
Section: Long-term Stabilitymentioning
confidence: 99%
“…Li et al demonstrated the first DJ phase perovskite based on formamidinium (FA) using the novel bifunctional molecule 1,4‐phenyl‐enedimethanammonium (PDMA) as an organic spacer. Ma et al reported a DJ phase perovskite based on 1,3‐propanediamine (PDA), which exhibited reduced inorganic layer spacing and negligible QW confinement effects, which resulted in improved efficiency.…”
Section: Comparison Of Champion Photovoltaic Performance Of Pda‐ Bdamentioning
confidence: 99%
“…[ 31 ] Whereas, most of the researchers focused on the design on the new type of low dimensional RP perovskite materials. [ 32–36 ] Yan et al prepared the 2D/3D bulk‐heterojunctions RP perovskite devices via introducing the S‐bearing thiophene‐2‐ethylamine spacer cation, exhibiting a stabilized PCE over 11% with negligible hysteresis. [ 32 ] Zhang and co‐workers enhanced the charge transport in 2D perovskites via 4‐fluorophenethylene lammonium (F‐PEA) and obtained a PCE over 13% for (F‐PEA) 2 MA 4 Pb 5 I 16 ‐based PSCs with high thermal stability.…”
Section: Introductionmentioning
confidence: 99%